Redox Balance in Cancer in the Context of Tumor Prevention and Treatment - Paweł Sutkowy; Przemysław Czeleń (Biomedicines)
Malignant neoplasms constitute a substantial health concern for the human population, currently ranking as the second leading cause of mortality worldwide. In 2022, approximately 10 million deaths were attributable to cancer, and projections estimate that this number will rise to 35 million in 2050. Consequently, the development of effective cancer treatments and prevention strategies remains a primary focus of medical research. In this context, the impacts on the redox balance are being considered. The objective of this study was to present the current knowledge on oxidation and reduction processes in cancer. This review discloses the intricate and multifaceted interplay of oxidoreductive systems during carcinogenesis, which engenders discordant findings in the domain of tumor prevention and treatment. This study also examines the controversies surrounding the use of antioxidants, including their impact on other therapeutic interventions. The review offers a comprehensive overview of the existing knowledge on the subject, concluding that personalized and precise anticancer therapies targeting the redox processes can serve as both effective diagnostic and therapeutic tools.